Young bodies and the Sex Education in Teacher training. Weaving equitative gender relation ships (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
In this article we present the reflections of different research of works in the educational field, where the gender perspective is privileged. Those Projects are based on the analysis of the experiences of students and teachers in relation to the Integral Sexual Education, in the formation in the Professorate of Primary School at the Institute of Teaching Formation, in the city of San Carlos de Bariloche. The seminar of Sexuality and Gender was established on a case studio through the analysis of the register of participant observation, conversations and interpretation of students realized in different workshops, since 2011 to 2016. The interventions of education in this case were related with the representations and images about the young bodies, sexuality and the relationships of gender. The reflections of this experience of the practice, the relats and other estheticprodutions of the students intertwined with the theorical frame work are some of the contribution that we develop in this article.
Keywords: gender(s); sexuality; body; youth; Sexual Education.